The organisational characteristics and knowledge management enabler towards employee entrepreneurial orientation in Klang Valley manufacturing industries - Kesavan, Nallaluthan (2018)
The aim of this study is to examine the relationship between organisational characteristics, knowledge management enabler, learning orientation and employee entrepreneurial orientation among the manufacturing industry employees in Klang Valley, Malaysia. The theoretical model based on Resource-Based Theory approach to the employee entrepreneurial orientation was developed. To answer the research questions, seven hypotheses were formulated. These are; (i) There is significant relationship between organisational characteristics and learning orientation, (ii) There is significant relationship between knowledge management enabler and learning orientation, (iii) There is significant relationship between learning orientation and employee entrepreneurial orientation, (iv) There is significant relationship between organisational characteristics and employee entrepreneurial orientation, (v) There is significant relationship between knowledge management enabler and employee entrepreneurial orientation, (vi) learning orientation mediates the relationship organisational characteristics and employee entrepreneurial orientation, and (vii) learning orientation mediates the relationship knowledge management enabler and employee entrepreneurial orientation. Self-administered questionnaires were distributed to the manufacturing industry employees. A total of 386 manufacturing employees of all levels were involved in this study, making an overall 25.73 percent response rate. This study utilised the Partial Least Squares Structural Equation Modelling (PLS-SEM) to establish the validity and reliability of the measurement model and test the relationships. The findings of the study showed that both organisational characteristics and knowledge management enabler have significant influences on employee entrepreneurial orientation. The results indicated that learning orientation has a mediating role in the relationship between organisational characteristics towards employee entrepreneurial orientation, and knowledge management enabler towards employee entrepreneurial orientation. The findings offered several theoretical and practical implications to employees and policy makers. The limitations of the study are addressed and recommendations for future research work also offered.